Effect of rare-earth (RE = La, Nd, Ce and Gd) doping on the piezoelectric of PZT(52:48) ceramics - N. Udomkan (2018)
The purpose of this research is to study the effect of doping some rare earth ions into PZT(52:48) ceramics. The ferroelectric Pb(ZrxTi1-x)O3ceramics are well-known as piezoelectric materials for electro-mechanical transducers such as ultrasonic generator, electronic buzzer, and stress sensor, etc. The highest piezoelectric coupling coefficients as well as maximum permittivity are located near the morphotropic phase boundary (MPB). The region of phase transition between the tetragonal and rhombohedral structures in the Pb(ZrxTi1-x)O3ceramic shows very adoptable piezoelectric characteristics due to the phase coexistence phenomena, and exhibits a sensitivity of properties to the preparation method, the composition, the firing temperatures and the kinds of additives. The purpose of this research is to study the effect of doping La, Nd, Ce and Gd into Pb(Zr0.52Ti0.48)O3ceramics prepared by solid state reaction. The properties include microstructure, physical properties, dielectric constant (εr) and piezoelectric properties (kpand Qm) of undoped and La, Nd, Ce and Gd doped PZT ceramics. Several effects, such as firing temperature, grain size and dopants, on the properties of PZT were also studied. The undoped PZT ceramics with Zr/Ti at 52/48 indicated the highest εr= 1969 and kp= 0.381 for La doping. Doping with La, Nd, Ce and Gd led to an improvement in the εrbut a reduced Qmvalue. The optimum values of electric properties were found in PZT (52/48) doped La with 10.0 mol% sintered at 1200°C for 2 h. © World Scientific Publishing Company.